Brexit - the 2016 referendum on European Union membership - Soares, António Goucha (2019)
This article explores the Brexit referendum, focusing on the political events that led to the vote, namely, the Conservative Party’s return to power, David Cameron’s attempts to appease the European divide within his party and the role played by the British Parliament in the whole process. It then discusses whether the referendum was the most suitable way to decide on European Union membership, considering the sovereignty of the British Parliament, as well as the contrast between representative democracy and direct democrac